Can common property resource system work in Zimbabwe? - Campbell, Bruce M.; Jong, W. de; Luckert, M.; Mandondo, A.; Matose, F.; Nemarundwe, N. (2002)
Common property resource (CPR) management approaches are now thought to provide a viable alternative to natural resource management. This article contains result of the investigations on common property issues for woodlands in communal areas in Zimbabwe. It reveals numerous cases showing a breakdown of local institutions for CPR management, and the lack of any emerging alternative institutions for such management. A number of economic, social and ecological factors contribute to these problems. It argues that current institutional systems are rooted in norm-based controls contrary to the formal rule-based systems that form the cornerstones of the proposed CPR systems. It suggests that interventions that propose CPR systems need critical analysis.